Réponses

2013-10-14T17:04:24+02:00
A) 3x-1=5
   3x=5+1
   3x=6      x=6/3  x=2
b) 2(x+5)=12-3x
     2x+10=12-3x
     2x+3x=12-10
     5x=2    x=2/5
c) 4(1-x)=6(x+3)
   4-4x=6x+18
     -4x-6x=18-4
       -10x=14      x=-14/10    x=-1,4
2013-10-14T17:05:45+02:00
a) 3x - 1 = 5
3x = 5 + 1
3x = 6
x = 6/3

b) 2(x + 5 ) = 12 - 3x
2 * x + 2 * 5 = 12 - 3x
2x + 10 = 12 - 3x
2x + 3x = 12 - 10
5x = 2
x = 2/5

c) 4(1 - x ) = 6 ( x + 3 )
4 * 1 + 4 * (-x) = 6 * x + 6 * 3
4 - 4x = 6x + 18
-4x - 6x = 18 - 4
-10x = 14
x = 14/-10